Deficiency of RARα Suppresses Decidualization via Downregulating CEBPB Transcription in Women With Recurrent Implantation Failure - Huang, Caiyi; Zhang, Qian; Ni, Tianxiang; Zhou, Tingting; Lv, Chunzi; Li, Yan; Yan, Junhao; Chen, Zi-Jiang (Frontiers in Endocrinology, 2022)
Background: Recurrent implantation failure (RIF) is a disease associated with endometrial receptivity dysfunction. Retinoic acid receptor alpha (RARα) is an important protein in many biological processes, such as differentiation and development. However, the exact underlying mechanism whereby RARα affects RIF remains unknown. This study investigated RARα expression and its contribution in the mid-luteal phase endometria of patients with RIF. Methods: The expression levels of RARα and CCAAT/enhancer binding protein (C/EBP) β in the endometria of the RIF and normal group were investigated using western blotting and immunohistochemistry. In in vitro experiments, immortal telomerase-transformed human endometrial stromal cells (T-HESCs) were incubated with medroxyprogesterone-17-acetate (MPA) and cyclic adenosine monophosphate (cAMP) for 4 days to induce decidualization. The expression levels of the decidualization markers prolactin (PRL) and insulin-like growth factor-binding protein-1 (IGFBP-1) were determined using quantitative polymerase chain reaction. RARα was knocked down using a small interfering RNA, and C/EBPβ was overexpressed from an adenoviral vector. The transcriptional regulation of CEBPB by RARα was determined by chromatin immunoprecipitation (ChIP) assay. Results: We found that the expression levels of RARα decreased in the mid-luteal endometria of RIF patients. After 4 days of decidualization induction in vitro, RARα knockdown impaired the decidualization of T-HESCs and downregulated the expression of C/EBPβ. The restoration of C/EBPβ expression rescued the RARα knockdown-induced suppression of T-HESC decidualization. In ChIP analysis of lysates from decidualized T-HESCs, the CEBPB promoter region was enriched in chromatin fragments pulled down using an anti-RARα antibody. However, the relationship between CEBPB transcription and RARα expression levels was only observed when the decidualization of T-HESCs was induced by the addition of cAMP and MPA. To identify the binding site of RARα/retinoid X receptor α, we performed luciferase assays. Mutation of the predicted binding site in CEBPB (-2,009/-1,781) decreased the transcriptional activity of the reporter. To confirm this mechanism, the expression levels of C/EBPβ in the mid-luteal endometria of RIF patients were determined and found to decrease with decreased RARα expression levels. Conclusion: A deficiency of RARα expression in the mid-luteal endometrium inhibits decidualization due to the downregulation of CEBPB transcription.